Genotoxic effect of simultaneous therapeutic exposure to polycyclic aromatic hydrocarbons and UV radiation - Malkova, Andrea; Borska, Lenka; Smejkalova, Jindra; Hamakova, Kvetoslava; Kremlacek, Jan; Svadlakova, Tereza; Borsky, Pavel; Holmannova, Drahomira; Fiala, Zdenek (JAT. Journal of applied toxicology, 2021)
Polycyclic aromatic hydrocarbons (PAHs) and ultraviolet radiation (UV) represent genotoxic factors that commonly occur in the living and working environment. The dermal form of exposure represents a significant part of the total load of dangerous chemical and physical environmental factors to which an organism is subjected. However, simultaneous dermal exposures to PAHs (pharmaceutical crude coal tar [CCT]) and UV (UVA and UVB) also have therapeutic uses. A typical example is Goeckerman therapy (GT) for psoriasis. The question of the therapeutic efficacy of GT and the related level of genotoxic danger is still under discussion. The aim of the present study was to compare four GT variants (G1-G4) in terms of efficacy and acceptable genotoxic hazard. Efficacy was expressed by the psoriasis area of severity index (PASI) score, genotoxic hazard by chromosomal aberration in peripheral lymphocytes. The lowest risk of genotoxic hazard and the lowest efficiency was observed in G1 variant (3% of the CCT and UVA + UVB). The efficacy of G2 (4% CCT and UVA + UVB), G3 (4% CCT and UVB), and G4 variants (5% CCT and UVA + UVB) was comparable. The highest risk of genotoxic hazard was found in the G3 variant. In the terms of sufficient efficacy and acceptable genotoxic hazard, a combination of 4% or 5% of CCT and UVA and UVB seems to be acceptable (variants G2 and G4).
Keywords: dehet uhelný; Lymphocytes; DNA Damage; lidé; poškození DNA; lymfocyty; psoriáza; Psoriasis; chromozomální aberace; Ultraviolet Rays; polycyklické aromatické uhlovodíky; Chromosome Aberrations; Polycyclic Aromatic Hydrocarbons; Coal Tar; ultrafialové záření; Humans